1995
DOI: 10.1143/jjap.34.5154
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oriented Pb(Zr, Ti)O3 Thin Films Prepared by Pulsed Laser Ablation on GaAs and Si Substrates with MgO Buffer Layer

Abstract: Highly [100]-oriented Pb(Zr, Ti)O3 (PZT) films were prepared on (100) GaAs and (100) Si substrates with MgO buffer layer by pulsed laser ablation (PLA). The depth profile of the constituent elements observed by X-ray photoelectron spectroscopy (XPS) shows that there are no remarkable interdiffusion and/or no formation of an alloying layer at both interfaces between PZT and MgO and between MgO and GaAs substrate. The [100]-oriented perovskite PZT films which exhibit the ferroelectric hysteresis loop were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Both the high mismatch of Ϫ22.5% between MgO ͑lattice constant a MgO ϭ4.21 Å) and Si ͑lattice constant a Si ϭ5.43 Å) and the large difference in thermal expansion coefficients (␣ MgO ϭ13.5ϫ10 Ϫ6 /°C vs ␣ Si ϭ4ϫ10 Ϫ6 /°C) in principle make the epitaxy of MgO on Si͑001͒ quite unlikely. As a consequence, there are few publications in which MgO/Si epitaxy is treated, either by laser ablation 9,[12][13][14][15] or other deposition techniques. 16 First studied almost 30 years ago 17,18 the epitaxy and magnetic properties of the Fe͑001͒/MgO͑001͒ system have received a lot of attention since then and nowadays can be considered a model system for the study of many fundamental magnetic properties.…”
mentioning
confidence: 99%
“…Both the high mismatch of Ϫ22.5% between MgO ͑lattice constant a MgO ϭ4.21 Å) and Si ͑lattice constant a Si ϭ5.43 Å) and the large difference in thermal expansion coefficients (␣ MgO ϭ13.5ϫ10 Ϫ6 /°C vs ␣ Si ϭ4ϫ10 Ϫ6 /°C) in principle make the epitaxy of MgO on Si͑001͒ quite unlikely. As a consequence, there are few publications in which MgO/Si epitaxy is treated, either by laser ablation 9,[12][13][14][15] or other deposition techniques. 16 First studied almost 30 years ago 17,18 the epitaxy and magnetic properties of the Fe͑001͒/MgO͑001͒ system have received a lot of attention since then and nowadays can be considered a model system for the study of many fundamental magnetic properties.…”
mentioning
confidence: 99%
“…However, Ishiguro et al [22] reported mixed h1 0 0i and h1 1 0i oriented epitaxial growth, with predominantly h1 0 0i oriented growth occurring at a substantially lower substrate temperature of 300 8C and higher oxygen pressure of 10 À4 Torr. Optimal conditions of 450 8C and 0.1-0.5 Torr were also reported for h1 0 0i oriented films, produced using an MgO target [23]. The substrate temperature reported for growth on GaAs were in better agreement with an almost universal setting of 350 8C [24,25], although the reported ambient pressures may over the same range as for the growth of MgO on Si.…”
Section: Pulsed Laser and Ablation Techniquementioning
confidence: 63%
“…Experimental evidence showed that the peak intensity of MgO h2 0 0i was greatly improved for the films deposited at O 2 pressure of 10 À2 Pa than 10 À3 Pa [27]. This result suggested that perfect h1 0 0i oriented MgO films could be deposited in low O 2 pressure, which is apparently different from that reported in the literature [140,141]. But high oxygen content leads to an increase in particles formation and consequently to a decrease in the deposition rate [88].…”
Section: Film Growth Mechanismmentioning
confidence: 69%
“…The crystallinity of MgO layer strongly depends on the oxygen pressure applied during depositions as reported previously [12]. However, the experimental conditions reported for deposition of oriented MgO layer are quite different [13][14][15][16][17][18]. For this reason and bearing in mind our previous experiences for deposition of oxide films, the oxygen pressure of 1 Pa was selected.…”
Section: Mgo Buffer Layer Depositionmentioning
confidence: 89%